Marketing Communication Model of International School in Post COVID-19 Pandemic - Zunan Setiawan; Ratih Pratiwi; Elfridawati Mai Dhuhani; Yusriah Yusriah; Evi Susilawati (Jurnal Komunikasi Profesional, 2023)
International School like Binus is an outstanding international school of Indonesia which other than the language using foreign language, they also participate in international event a lot. However, it contains some problem in the educational system, with Krippendorf’s content analysis, Author is able to discover that English linguistic bias grows up boldly in international school because they lack actual bilateral relationship. That bilateral relationship can be manifested through human resources having important occupation in foreign school or Binus winning international competition.